Quick Respond-Based Case Note Management System: A Case Study for File Record Unit - Tiong, Wei King; Hooi, Mun Hoe; Sze, San Nah; Chiew, Kang Leng; Izzatul Nabila, Sarbini; Goh, Say Leng; Sze, Jeeu Fong (Semarak Ilmu Publishing, 2024)
The common and major problem with public hospitals in Malaysia is patients’ case note management, which includes tracking and updating the details of the case notes daily. Currently, the hospital is still adopting the manual method of managing the case notes which is time-consuming and prone to human errors. This paper proposed a quick respond-based case note management system for a public general hospital in Malaysia. In this project, the Quick Respond code is used as an identification or tag for the case note when the staff is looking for the case note in the existing in-house management system. This is useful for reducing the steps of manual work by only scanning the QR code at the speed of a second. The proposed system contains three modules, that are QR code printing, QR code scanning, and reporting. Our findings show that the time needed to manage the case notes is reduced greatly with the deployment of the system. The system also managed to lighten the work burden faced by the nurses at the hospital.